Assessment of Normal Sagittal Alignment of the Spine and Pelvis in Children and Adolescents - Ghandhari, Hasan (Hindawi Publishing Corporation, 2013)
Aim. We aimed to determine spinopelvic balance in 8–19-year-old-people in order to assess pelvic and spinal parameters in sagittal view. Methods. Ninety-eight healthy students aged 8–19 years, who lived in the central parts of Tehran, were assessed. Demographic data, history of present and past diseases, height (cm), and weight (kg) were collected. Each subject was examined by an orthopedic surgeon and spinal radiographs in lateral view were obtained. Eight spinopelvic parameters were measured by 2 orthopedic spine surgeons. Results. Ninety-eight subjects, among which 48 were girls (49%) and 50 boys (51%), with a mean age of 13.6 ± 2.9 years (range: 8–19) were evaluated. Mean height and weight of children were 153.6 ± 15.6 cm and 49.9 ± 13.1 kgs, respectively. Mean TK, LL, TT, LT, and PI of subjects were 37.1 ± 9.9°, 39.6 ± 12.4°, 7.08 ± 4.9°, 12.0 ± 5.9°, and 45.37 ± 10.7°, respectively. Conclusion. Preoperation planning for spinal fusion surgeries via applying PI seems reasonable. Predicating “abnormal” to lordosis and kyphosis values alone without considering overall sagittal balance is incorrect. Mean of SS and TK in our population is slightly less than that in Caucasians.